(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes the state of land resources in the Russian Federation, the Republic of Bashkortostan; The structure of lands in state and municipal ownership is determined; The main directions with the emergence of management of land problems of the municipality are identified.